Persistent Chronic Periprosthetic Joint Infection Treated with Three-Stage Revision Hip Arthroplasty: A Case Report - Nurul Ramadian; Jifaldi Afrian Maharaja Dinda Sedar (Universitas Airlangga, 2023)
Background: Periprosthetic Joint Infection (PJI) is a dreadful complication of primary Total Hip Arthroplasty (THA). Following revision THA, up to 17% of revision THA can be complicated with PJI. Three-stage revision should only be done if simple debridement fails to treat PJI. Here we present a rare case of persistent PJI, treated with three-stage revision and bone grafting.Case Report: A thirty-seven-year-old female patient came with a chief complaint of hip pain four months ago. Four years ago, the patient had a right column femur fracture and was treated with THA. One year afterward, the implant was infected, and the hip was debrided. One year later, the infection symptom recurred, and three-stage revision hip arthroplasty was planned with one year delay for each stage: removal of the implant, replacement of spacer, and reimplantation. The acetabular bone was augmented using autograft from the iliac wing during reimplantation. After reimplantation, the pain subsides, and the patient can walk normally again.Discussion: Previous studies have found various risk factors that might contribute to the failure of two-stage revision arthroplasty. The infecting bacteria is one of the major risk factors, and therefore appropriate antibiotic is important. Augmentation of bone graft can also supplement acetabular bone loss during failed THA as it helps as a scaffold for bone healing.Conclusion: Three-stage revision hip arthroplasty after PJI using bone graft for augmentation is possible with a good result.